The influence of food consumption and socio-economic factors on the relationship between zinc and iron intake and status in a healthy population. Issue 14 (23rd June 2017) - Knez, Marija; Nikolic, Marina; Zekovic, Milica; Stangoulis, James CR; Gurinovic, Mirjana; Glibetic, Maria
Abstract: Objective: To examine Zn and Fe nutritional status of a healthy population by means of anthropometric, dietary and biochemical measurements and to investigate the relationship of usual Zn and Fe dietary intakes to Zn and Fe status. In addition, to examine the impact of food choices and socio-economic factors on Fe and Zn dietary intakes and status with the aim to identify groups at risk of dietary deficiency and suggest factors that may influence the status of these nutrients. Design: Food consumption was assessed by 24 h recall questionnaires. Twenty biochemical parameters were measured, of which Hb, haematocrit, erythrocyte count and plasma concentrations of Fe and Zn were directly related to Fe and Zn nutrition. The prevalence of study participants with inadequate micronutrient intakes was calculated using the Estimated Average Requirement cut-point method. Setting: Serbia, Europe. Subjects: Apparently healthy adults (25–65 years of age). Results: Mean daily Zn and Fe intakes were 9·1 mg and 11·6 mg for males and 7·3 mg and 9·4 mg for females, respectively. Five per cent of the study population had inadequate dietary Fe intake and 15–25 % had inadequate Zn intake. Lower Hb concentrations were measured in women with lower Zn intakes. No differences in Fe and Zn intakes and status among various socio-economic groups were observed, except for Fe intake between the low-income and affluent groups. Conclusions: Regular follow-ups are needed to ensure that potential deficiencies of Zn and Fe do get recognized and addressed in a timely manner.